Investigation into inconsistent lateralisation of language functions as a potential risk factor for language impairment - Bradshaw, AR; Woodhead, ZVJ; Thompson, PA; Bishop, DVM (Wiley, 2019)
Disruption to language lateralisation has been proposed as a cause of developmental language impairments. In this study, we tested the idea that consistency of lateralisation across different language functions is associated with language ability. A large sample of adults with variable language abilities (N = 67 with a developmental disorder affecting language and N = 37 controls) were recruited. Lateralisation was measured using functional transcranial Doppler sonography (fTCD) for three language tasks that engage different language subprocesses (phonological decision, semantic decision and sentence generation). The whole sample was divided into those with consistent versus inconsistent lateralisation across the three tasks. Language ability (using a battery of standardised tests) was compared between the consistent and inconsistent groups. The results did not show a significant effect of lateralisation consistency on language skills. However, of the 31 individuals showing inconsistent lateralisation, the vast majority (84%) were in the disorder group with only five controls showing such a pattern, a difference that was higher than would be expected by chance. The developmental disorder group also demonstrated weaker correlations between laterality indices across pairs of tasks. In summary, although the data did not support the hypothesis that inconsistent language lateralisation is a major cause of poor language skills, the results suggested that some subtypes of language disorder are associated with inefficient distribution of language functions between hemispheres. Inconsistent lateralisation could be a causal factor in the aetiology of language disorder or may arise in some cases as the consequence of developmental disorder, possibly reflective of compensatory reorganisation.